Social Capital Between Restaurant Owners and Fish Traders at the Lappa Fish Auction Place - Muhammad Syafri; Syamsu A Kamaruddin; Supriadi Torro; Arlin Adam (Cendekiawan Indonesia Timur, 2026)
The relationship between restaurant entrepreneurs and fish traders is not only transactional economic, but also a social relationship based on trust, local cultural values, and informal social networks. The approach used in this study is a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The theories used in the analysis include symbolic interaction theory (Blumer), social exchange theory (Homans), and social capital theory (Coleman). The results of the study show that the forms of interaction that occur between the two parties include long-term subscription practices, timely payments, and close communication based on local values such as siri', cooperation, and mutual trust. This social interaction has been proven to be able to produce stability in the supply and distribution of fresh fish, as well as strengthen the local economic resilience of coastal communities. The existence of social capital is the main key in forming a network of cooperation that is not only economically profitable but also strengthens social solidarity. Thus, economic practices at TPI Lappa reflect the integration between the economic system and local culture that characterizes the Bugis-Makassar coastal community.